Mapping the Furnace Room - Ghaffar, Asher (UnderCurrents: Journal of Critical Environmental Studies, 2006)
When he was a child he had a passion for mapping the house, the earth: archaeology, destratifying and stratifying. Imagining maps in his cobbled mind. He walked around the block with a question in his mind that had been bottled in the furnace of the house. A question like “who am I, here?” and upon arriving at the same point on the block, the same question would blaze up. An inflammatory question forged in the furnace of his house when he went to fill a pitcher with distilled water and clambered over a mountain of photo albums to arrive at the distiller.